AP Ir. Dr. Mohd Hafizi, Atirah announced winners of CITREx 21 Best Awards - Dina Diyana, Rastam Tan (2021)
PEKAN, 7 April 2021 – A lecturer from the Faculty of Mechanical and Automotive Engineering Technology (FTKMA), Associate Professor Ir. Dr. Mohd Hafizi Zohari received a gold medal and two special awards which are the FTKMA Creativity and Innovation Awards (First Place) and Best of the Best Special Award (Staff Category) in the Creation, Innovation, Technology & Research Exposition (CITREx) 2021 organised by the Research and Innovation Department (JPI), Universiti Malaysia Pahang (UMP).